2010
DOI: 10.1107/s0108270110009121
|View full text |Cite
|
Sign up to set email alerts
|

Benzene-1,4-diboronic acid–4,4′-bipyridine–water (1/2/2)

Abstract: In the presence of water, benzene-1,4-diboronic acid (1,4-bdba) and 4,4'-bipyridine (4,4'-bpy) form a cocrystal of composition (1,4-bdba)(4,4'-bpy)(2)(H(2)O)(2), in which the molecular components are organized in two, so far unknown, cyclophane-type hydrogen-bonding patterns. The asymmetric unit of the title compound, C(6)H(8)B(2)O(4).2C(10)H(8)N(2).2H(2)O, contains two 4,4'-bpy, two water molecules and two halves of 1,4-bdba molecules arranged around crystallographic inversion centers. The occurrence of O-H..… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Molecules used for co-crystallization studies Although the syn,syn-conformer is found in the boronic acid-carboxylate synthon [28], the existence of this conformer with N-heterocycles is relatively rare and usually happens as a chance or with the assistance from lattice water [25,27,29]. The present study is an extension of our earlier work on the synthon preferences of various functional groups towards a 1,2,4-triazole containing drug-alprazolam (ALP) [30].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Molecules used for co-crystallization studies Although the syn,syn-conformer is found in the boronic acid-carboxylate synthon [28], the existence of this conformer with N-heterocycles is relatively rare and usually happens as a chance or with the assistance from lattice water [25,27,29]. The present study is an extension of our earlier work on the synthon preferences of various functional groups towards a 1,2,4-triazole containing drug-alprazolam (ALP) [30].…”
Section: Introductionmentioning
confidence: 93%
“…PhenylScheme 2 Various conformations possible for the -B(OH) 2 functionality. boronic acids have been shown to form OH···N hydrogen bonds with several pyridine based linear spacer ligands [25,27]. The possible non-covalent interactions with N-donor compounds together with the conformational flexibility render this functionality an interesting one in the tool kit of the crystal engineer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong hydrogen bond donor ability and relatively weak hydrogen bond acceptance of boric acid and its derivatives makes them excellent candidates for crystal engineering and co-crystal formation. [1][2][3][4] Simple aryl boronic acids tend to form cyclic hydrogen-bonded dimers in the solid state and this motif results in additional hydrogen atoms capable of interacting with guest species. A search of the 2017 version of the Cambridge Structural Database (CSD 5 ) reveals some 14 neutral organic co-crystal structure determinations incorporating boric acid itself.…”
Section: Introductionmentioning
confidence: 99%
“…A search of the 2017 version of the Cambridge Structural Database (CSD 5 ) reveals some 14 neutral organic co-crystal structure determinations incorporating boric acid itself. Boric acid co-crystals are typically formed with nitrogen bases such as pyridines or imidazoles, 3,6,7 or highly polar oxygen acceptors such as triphenylphosphine oxide. 8 There are also a number of fascinatingly complex inorganic and ionic boric acid co-crystals such as tetraethylammonium carbonate urea clathrate bis(boric acid) monohydrate.…”
Section: Introductionmentioning
confidence: 99%